2021
DOI: 10.3390/educsci11090557
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Future Education Model—Strategies Drawn from Teaching during the COVID-19 Pandemic

Abstract: As they emerge from the pandemic, universities worldwide are evaluating the adaptations in the education sector during the pandemic and determining their course of action for the future. In this work, drawing on the lessons from four courses across two different universities, a survey of over 300 students, and the literature, we present strategies for successfully implementing a flexible blended education format. The survey revealed that the performance of the cohort taking the course during the pandemic perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 69 publications
0
17
0
1
Order By: Relevance
“…A number of studies investigated how students in different areas of the world adapted to the sudden shift to remote learning during the pandemic. Both Srinivasan, Ramos, and Muhammad (2021) and Castro and George (2021) reported that many respondents were dissatisfied with exclusive online learning, citing the perceived negative impact on their social and academic engagement with peers and faculty. The researchers found that majorities were open to hybrid learning models, however.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of studies investigated how students in different areas of the world adapted to the sudden shift to remote learning during the pandemic. Both Srinivasan, Ramos, and Muhammad (2021) and Castro and George (2021) reported that many respondents were dissatisfied with exclusive online learning, citing the perceived negative impact on their social and academic engagement with peers and faculty. The researchers found that majorities were open to hybrid learning models, however.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Altogether, university teaching in a digitalized context requires intense and complex preparation as well as strategic planning. In [59], the course design, pedagogical strategies incorporating active learning and providing a sense of online community, infrastructure for delivery and training, and incorporating activities that support student wellbeing were identified as success factors for digital education. In [60], student-student and instructor-student dialogues are identified as success factors.…”
Section: Discussionmentioning
confidence: 99%
“…The convergence of technologies has been used to operationalize hybrid classes. In a hybrid class, an instructor combines the benefits of classroom and online instruction [14]. In the Fall of 2021, still under pandemic conditions, a hybrid version of this course was offered.…”
Section: Lesson Planning and Operational Strategiesmentioning
confidence: 99%
“…A variety of pedagogical approaches were considered to teach the course. These include active learning, project-based learning, inquiry-based learning, problem solving-based approach and small group learning [14]. The active learning environment was preferred because it allows students to participate and be engaged while learning.…”
Section: Lesson Planning and Operational Strategiesmentioning
confidence: 99%